Gene organization around the phenylalanyl-transfer ribonucleic acid synthetase locus in Escherichia coli. - Comer, M M (1981)
The organization of seven genes located at about 38 min on the genetic map of Escherichia coli was examined; these genes included pheS and pheT, which code for the alpha and beta subunits of phenylalanyl-transfer ribonucleic acid synthetase, and thrS, the structural gene for threonyl-transfer ribonucleic acid synthetase. Deletion mutants were isolated from an F-prime-containing merodiploid strain and were characterized genetically. Seventeen different kinds of deletions extending into pheS of pheT were identified. These deletions unambiguously defined the gene order as aroD pps himA pheT pheS thrS pfkB. Mutants with deletions covering either pheS or pheT, but not both, were analyzed further by assay of phenylalanyl-transfer ribonucleic acid synthetase. The phenotype of the mutants with a deletion from pfkB through pheS was anomalous; although the pheT gene was apparently still present, its product, the beta subunit, was much reduced in activity.